3′-Terminal 2′-O-methylation of lung cancer miR-21-5p enhances its stability and association with Argonaute 2. Issue 13 (15th June 2020) - Liang, Hongwei; Jiao, Zichen; Rong, Weiwei; Qu, Shuang; Liao, Zhicong; Sun, Xinlei; Wei, Yao; Zhao, Quan; Wang, Jun; Liu, Yuan; Chen, Xi; Wang, Tao; et al.
Abstract: Methylation of miRNAs at the 2′-hydroxyl group on the ribose at 3′-end (2′- O -methylation, 2′Ome) is critical for miRNA function in plants and Drosophila. Whether this methylation phenomenon exists for mammalian miRNA remains unknown. Through LC–MS/MS analysis, we discover that majority of miR-21-5p isolated from human non-small cell lung cancer (NSCLC) tissue possesses 3′-terminal 2′Ome. Predominant 3′-terminal 2′Ome of miR-21-5p in cancer tissue is confirmed by qRT-PCR and northern blot after oxidation/β-elimination procedure. Cancerous and the paired non-cancerous lung tissue miRNAs display different pattern of 3′-terminal 2′Ome. We further identify HENMT1 as the methyltransferase responsible for 3′-terminal 2′Ome of mammalian miRNAs. Compared to non-methylated miR-21-5p, methylated miR-21-5p is more resistant to digestion by 3′→5′ exoribonuclease polyribonucleotide nucleotidyltransferase 1 (PNPT1) and has higher affinity to Argonaute-2, which may contribute to its higher stability and stronger inhibition on programmed cell death protein 4 (PDCD4) translation, respectively. Our findings reveal HENMT1-mediated 3′-terminal 2′Ome of mammalian miRNAs and highlight its role in enhancing miRNA's stability and function.